Screening of BCOR‐CCNB3 sarcoma using immunohistochemistry for CCNB3: A clinicopathological report of three pediatric cases. (3rd June 2015) - Shibayama, Takahiro; Okamoto, Takeshi; Nakashima, Yasuaki; Kato, Takaaki; Sakurai, Takaki; Minamiguchi, Sachiko; Kataoka, Tatsuki R.; Shibuya, Shinsuke; Yoshizawa, Akihiko; Toguchida, Junya; Haga, Hironori
<x xml:space="preserve">Abstract</x> BCOR‐CCNB3 sarcoma is a recently recognized tumor morphologically and clinically simulating Ewing sarcoma. We herein retrospectively collected clinicopathologic data on BCOR‐CCNB3 sarcoma in the Kyoto University Hospital over the last 10 years. Three (20%) bone sarcomas were revealed to be diffusely positive for CCNB3 immunohistochemistry among 15 pediatric cases of undifferentiated sarcoma morphologically similar to Ewing sarcoma, while the other cases showed completely negative staining. The three patients with immunohistochemically CCNB3‐positive tumors were all male, aged between 11 and 17, and confirmed to have the BCOR‐CCNB3 fusion transcript by RT‐PCR. Radiologically, all cases had well‐demarcated solid masses with bone destruction. Although the tumors were basically small round cell tumors, less monomorphic histological patterns such as short spindle cells, a myxoid matrix, and hemangiopericytoma‐like pattern were also observed in both biopsy and resected specimens. Two patients achieved a complete response after chemotherapy for Ewing sarcoma and osteosarcoma, respectively. These results demonstrated that the application of CCNB3 immunostaining was useful for differentiating BCOR‐CCNB3 from a group of 'Ewing‐like sarcomas' and may contribute to the evaluation of treatment strategies for bone sarcomas.